P–783 Clinical, obstetric and perinatal outcomes after vitrified-warmed euploid blastocyst transfer are independent of cryo-storage duration. (6th August 2021) - Maggiulli, R; Cimadomo, D; Dovere, L; Innocenti, F; Albricci, L; Soscia, D; Giancani, A; Sanges, F; Amendola, M G; Tacconi, L; Nastri, G; Morgante, V; et al.
Abstract: Study question: Is cryo-storage duration associated with the outcomes after vitrified-warmed euploid single blastocyst transfer? Summary answer: Lower live-birth-rates from blastocysts cryo-stored for periods longer than 3-months are mostly imputable to the worse quality of the embryos being warmed across sequential transfers. What is known already: Blastocyst vitrification is crucial in modern IVF. Given its widespread application, a constant comprehensive monitoring of its effect on reproductive outcomes is pivotal. For instance, the effect of cryo-storage duration on embryo implantation potential, gestational and perinatal outcomes is object of a still ongoing investigation. The evidence in this regard are contrasting especially with regard to similar or decreased live birth rates among blastocysts subject to long-term cryo-storage. When investigating the neonatal outcomes, instead, no impact of blastocyst cryo-storage duration has ever been reported to date. Yet, data on euploid blastocysts and adjusted for quality and full-blastulation day are needed. Study design, size, duration: Retrospective observational study. We included 2688 vitrified-warmed euploid single blastocyst transfers. The primary outcome was the live-birth-rates (LBR) according to cryo-storage duration clustered as ≤ 60, 61–90, 91–180, 181–360, 361–720, 721–1080 and >1080-days. The secondary outcomes were the miscarriage rate, the rates of gestational and perinatal issues among the deliveries, and the mean gestational age and birthweight among the babies born. All data were adjusted for confounders through linear or logistic regression analyses. Participants/materials, setting, methods: We included all vitrified-warmed transfers (range:1–8) conducted between May–2013 and March–2020 by 1884 patients (age:38±3yr) undergoing one blastocyst stage PGT-A cycle and obtaining ≥1 euploid embryo at our private clinic. Among putative confounders, only the number of sequential transfer from the same patient, blastocyst quality (Gardner's scheme) and full-blastulation day (5–7) significantly associated with the LBR through univariate regressions. No association was reported for sperm factor, maternal age, incubator, and culture media. Main results and the role of chance: The LBR of euploid blastocysts cryo-stored for ≤60-days was 49.4% (N = 319/646) versus 48.7% (N = 292/599; OR:0.98, 95%CI:0.78–1.21, p=0.82) between 61–90-days, 42.9% (N = 291/679; OR:0.77, 95%CI:0.62–0.96, p=0.02) between 91–180-days, 41.7% (N = 169/405; OR:0.73, 95%CI:0.57–0.94, p=0.02) between 181–360-days, 34.7% (N = 50/144; OR:0.55, 95%CI:0.37–0.79, p<0.01) between 361–720-days, 53.4% (N = 63/118; OR:1.17, 95%CI:0.79–1.74, p=0.42) between 721–1080-days, and 50.5% (N = 49/97; OR:1.05, 95%CI:0.68–1.60, p=0.83) for >1080-days. However, when these data were adjusted for blastocyst quality and full-blastulation day, all the multivariate-OR were not-significant. Indeed, the longer the cryo-storage period the worse the quality of the euploid blastocysts transferred (e.g. AA-blastocysts were 74% among embryos cryo-stored for ≤90-days, but always <70% for embryos cryo-stored for longer periods, p < 0.01; similarly, day5-blastocysts were ∼50% among embryos cryo-stored for ≤90-days, but always <50% for embryos cryo-stored for longer periods, p = 0.02). The miscarriage-rate (overall 14%, ranging 7–18%) was not associated with cryo-storage duration already from univariate regressions. Also the gestational (overall 6%, ranging 0–8%) and perinatal issues rates (overall 3%, ranging 0–5%) were not associated with cryo-storage duration already from the univariate regressions. Neither the gestational age nor the birthweight showed significant associations with cryo-storage duration, as confirmed by linear regressions. In fact the rate of newborns whose weight was normal-for-gestational-age was similar across all cryo-storage duration groups (overall 81%, ranging 80–83%). Limitations, reasons for caution: The prevalence of first transfers decreases from ≥95% for procedures conducted ≤90-days from vitrification to 71%, 39%, 22% and 4% for procedures conducted between 91–180, 181–360, 361–720 and >720-days, respectively. However, also the sequential number of transfer was not associated with the LBR when adjusted for blastocyst-quality and full-blastulation day. Wider implications of the findings: Cryo-storage by vitrification is confirmed safe in the hands of experienced operators, and its duration does not impact any outcome. This information is valuable for freeze-all cycles, but also for women cryo-preserving surplus embryos for second pregnancies; in this regard, 6.8% of the patients in this study delivered ≥2 LBs. Trial registration number: Not applicable